Diagnosing Urban Resilience in an Evolutionary Approach - Jania, Agnieszka (Acta Universitatis Lodziensis. Folia Oeconomica, 2021)
Cities, although defined as the driving force of economies, function in changing conditions, including crisis-generating. In addition to their broad generic range, their simultaneous course is also important. Some cities are characterized by the adaptation potential, but others are subject to broadly understood degradation. Nevertheless, it becomes necessary to constantly adapt their structures in the context of the attainment (including maintenance) of local development. As a consequence, it is important to increase the scientific achievements on the response of city systems to disturbances (which often requires an individual approach).Therefore, the subject of the article concerns the diagnosis of urban resilience with an emphasis on the evolutionary approach. The main research goal refers to the identification of the conceptual framework of urban resilience, as well as examples of ways to diagnose it, including in the evolutionary approach. It has been decomposed into five sub‑goals:– defining urban resilience with an overview of research approaches within the urban resilience concept;– detailing the research perspectives in the field of the evolutionary approach relating to the concept of urban resilience with emphasis on the model of the adaptation cycle;– outline of the research context and, at the same time, ways of diagnosing urban resilience, distinguishing individual research approaches;– analysing structured examples of diagnosing urban resilience in the evolutionary approach;– proposing a new methodology in Polish conditions for determining urban resilience according to the evolutionary approach within the adaptation cycle model (in the economic and technological dimension).Thus, it became possible to define the standards adopted in the field of urban resilience research to date, as well as for future scientific publications and studies for the needs of economic practice. Moreover, on their basis, a new method was proposed for determining urban resilience in Polish conditions. It is an attempt to adapt elements of foreign research enriching domestic research.The methodological layer of the research includes a desk research in the field of literature concerning the concept of urban resilience. It applies to both Polish and foreign research centers. On the basis of the conducted research, the author states that the methods oriented at diagnosing urban resilience are characterized by a lack of uniformity. Consequently, the concept is applied in a variety of ways to a wide range of aspects of urban development. In order to organize the issues in question, a methodology is proposed to support the diagnosis of urban resilience in the economic and technological dimension. It was based on structured research methods used in several of the references cited. Additionally, it is useful for undertaking further, more advanced studies on urban resilience, i.e. context-oriented. Ultimately, research will be conducted on the impact of business projects implemented in post-industrial areas in cities on urban resilience. Thus, the article presents research, some of which can be considered as an additional pilot. They constitute a starting point for further research on urban resilience, including its measurement.